MANAJEMEN PEMBERIAN KREDIT PENSIUN PADA PT. BANK BTPN PURNA BAKTI - Handayani, Rina Nurul; Situmorang, Dokman Marulitua (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2023)
This research aims to find out the conditions that must be met by retirees when applying for credit, find out the mechanism of the credit granting process, find out the obstacles experienced when giving credit to retirees, overcome obstacles in the credit granting process. The data in this research was taken from interviews and documentation. The data analysis technique used in this research is the descriptive analysis method. This research was conducted by evaluating data on the credit granting process. The results of the research are that external obstacles include, customers not fulfilling the terms and conditions specified in the credit agreement and also customers having difficulty understanding information regarding credit services offered by PT. Bank BTPN Purna Bakti Tanjung Priok Branch. This can be overcome by providing brochures regarding credit, posting credit requirements on notice boards that are adjusted based on applicable regulations and regularly holding outreach to discuss pension credit or visiting customers' homes directly.